The grafting of triploid watermelon is an advantageous alternative to soil fumigation by methyl bromide for control of Fusarium wilt - Miguel, Alfredo; Maroto Borrego, José V.; San Bautista, Alberto; Baixauli, Carlos; Cebolla, Vicent; Pascual, B.; López-Galarza, Salvador; Guardiola, J. L. (2017)
Yield and fruit characteristics of grafted plants of the ‘Reina de Corazones’ watermelon cultivar (Citrullus lanatus (Thunb.) Matsum and Nakai), grown in Fusarium-infestated soils, were determined in a series of experiments performed in the 8-year period 1993–2000. The experiments were performed in the coastal area south Valencia, Spain, in soils with a clay content ranging from 16 to 38%. Plant survival and yield were the highest in plants grafted onto several Cucurbita maxima × Cucurbita moschata hybrids and onto ‘Jover’ and ‘Bodi 1’ C. moschata cultivars. The survival ratio of the plants grafted onto ‘Shintoza’ rootstock (C. maxima × C. moschata) was 93%, while the mean yield in an early production cycle with harvests extending from the end of June to mid-August was 89,000 kg ha−1. The ‘Shintoza’ rootstock increased fruit size compared to the non-grafted plants, and improved yield stability by decreasing the coefficient of variation to 20%. The use of ‘Shintoza’ rootstock had no effect on the soluble solids concentration of the central endocarp, and did not increase the development of yellowish bands in the flesh or the internal breakdown of the endocarp. The use of this rootstock is an advantageous alternative to soil fumigation by methyl bromide for the control of Fusarium wilt in watermelon production, as it is cheaper and safer, and the yields are higher and more reliable.